MOS-ONLY AUTOMATION TECHNIQUE WITH AN EXEMPLARY MOS-ONLY BP/LP AGILE FILTER DESIGN - (:unkn) unknown (ISTANBUL UNIV, FAC ENGINEERING, 2017)
In this work, a systematic of the automation in the result of the re-obtained small signal parameters based on SPICE and CADENCE-SPECTRE is presented for MOS-Only circuits. Accuracy of the re-obtained parameters was improved by re-formulating in the basis of SPICE and CADENCE-SPECTRE. Moreover, piece-wise polynomial regressive models are presented for g(ds), g(m) and I-ds. Also, performance of the models is compared with conventional expressions. Success of the given MOS-Only design automation based on re-obtained small signal parameters is verified with an exemplary new agile filter.
Keywords: MOS-Only; polynomial; SPICE; CADENCE-SPECTRE; CMOS OP-AMP